Peripheral blood mononuclear cells contribute to myogenesis in a 3D bioengineered system of bone marrow mesenchymal stem cells and myoblasts - Scala, Pasqualina; Manzo, Paola; Lamparelli, Erwin Pavel; Lovecchio, Joseph; Ciardulli, Maria Camilla; Giudice, Valentina; Selleri, Carmine; Giordano, Emanuele; Rehak, Laura; Maffulli, Nicola; Della Porta, Giovanna (Frontiers in Bioengineering and Biotechnology, 2023)
In this work, a 3D environment obtained using fibrin scaffold and two cell populations, such as bone marrow-derived mesenchymal stem cells (BM-MSCs), and primary skeletal muscle cells (SkMs), was assembled. Peripheral blood mononuclear cells (PBMCs) fraction obtained after blood filtration with HemaTrate® filter was then added to the 3D culture system to explore their influence on myogenesis. The best cell ratio into a 3D fibrin hydrogel was 1:1 (BM-MSCs plus SkMs:PBMCs) when cultured in a perfusion bioreactor; indeed, excellent viability and myogenic event induction were observed. Myogenic genes were significantly overexpressed when cultured with PBMCs, such as MyoD1 of 118-fold at day 14 and Desmin 6-fold at day 21. Desmin and Myosin Heavy Chain were also detected at protein level by immunostaining along the culture. Moreover, the presence of PBMCs in 3D culture induced a significant downregulation of pro-inflammatory cytokine gene expression, such as IL6. This smart biomimetic environment can be an excellent tool for investigation of cellular crosstalk and PBMC influence on myogenic processes.